Role of the general practitioner in improving rural healthcare access: a case from Nepal - Bikash Gauchan; Stephen Mehanni; Pawan Agrawal; Mandeep Pathak; Santosh Dhungana (BMC, 2018)
Abstract Background There is a global health workforce shortage, which is considered critical in Nepal, a low-income country with a predominantly rural population. General practitioners (GPs) may play a key role improving access to essential health services in rural Nepal, though they are currently underrepresented at the district hospital level. The objective of this paper is to describe how GPs are adding value in rural Nepal by exploring clinical, leadership, and educational roles currently performed in a rural district-level hospital. Case presentation We perform a descriptive case study of clinical and non-clinical services offered at Bayalpata Hospital prior to and following the initiation of GP-level services in 2013. Bayalpata is a district-level public hospital managed through a public private partnership by the nonprofit healthcare organization Possible. We found that after general practitioners were hired, additional clinical services included continuous emergency obstetric care, major orthopedic surgeries, appendectomy, tubal ligation, and vasectomy. This time period was associated with increased emergency department visits, inpatient admissions, and institutional birth rate in the hospital's catchment area. Non-clinical contributions included the development of a continuing medical education curriculum and implementation of a series of quality improvement initiatives. Conclusions GPs have potential to bring significant value to rural district hospitals in Nepal. Clinical impact may include expanded access to surgical and emergency obstetric services, which would more fully align with local health needs, and could further reduce Nepal's maternal mortality rate. Task-shifting and structured training programs would be required to increase orthopedic surgery capacity, but this would contribute to meeting local healthcare needs. Non-clinical impact may include supervision of health workers and leadership in continuing medical education and quality improvement initiatives. These changes can lead to improved health worker recruitment and retention in rural posts. Limitations include generalizability of our results to other district hospitals in Nepal and lack of data from control hospitals. This analysis provides an additional perspective on the potential value GPs can add in rural Nepal, through provision of a wide range of clinical and non-clinical services. It supports the expansion of GPs to additional district hospitals in Nepal's public sector.